PENGARUH MODEL ASUHAN KEPERAWATAN GIGI PENCEGAHAN SEKUNDER TERHADAP STATUS KESEHATAN GIGI IBU HAMIL (Studi Kasus Di Puskesmas Penebel I Tabanan) - Ida Bagus Putu Putra Kencana (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Background : Gingivitis is the initial form of periodontal disease. Gingivitis at the time of pregnancy is an independent risk factor for premature delivery and underweighed babies. From the interviews of the dental nurse in Puskesmas, it is said that there has not been any implementable model for pregnant women with gingivitis. Therefore, the researcher is interested to develop the model secondary preventive dental care which can be implemented for pregnant women with gingivitis.  Objective : to analyze the effectiveness of Mentoring Model of Secondary Dental Care Prevention towards GI, OHI-S, CPITN, PHP, Knowledge, Attitude, and Behavior of pregnant women suffering from gingivitis.  Method : This research use true experiment method with pre and post test design in intervention group and control group. The research sample used purposive sampling technique. The total members of sample are 60, which 30 of there are in intervention group and other 30 in control group. The measurement is done before and after intervention used questionnaire, gingivitis index, OHI-S, CPITN and PHP. The data was analyzed in univariate while bivariate manner using Chi-Square test   Result : After the implementation of Mentoring Model of Secondary Dental Care Prevention, there is a change in bad GI into good GI at 66.7%, a change from bad CPITN into good CPITN at 73.9%, a change from bad OHI-S into good OHI-S at 68.4%, a change from a bad knowledge into good knowledge at 57.9%, a change from bad attitude into good attitude at 89.5% and a change from bad actions into good actions at 75%. Conclusion : Mentoring Model of Secondary Dental Care Prevention is effective towards GI, CPITN, OHI-S, PHP, Knowledge, Attitude, and Behavior so that int can be used as alternative or intervention model to maintain dental and oral health in pregnant women.